1997
DOI: 10.1177/00220345970760080901
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Parathyroid Hormone Administration Stimulates Bone Formation in the Mandibles of Aged Ovariectomized Rats

Abstract: Intermittent administration of parathyroid hormone (PTH) is known to stimulate bone formation in many skeletal sites and is being investigated as a possible therapeutic agent for the treatment of osteopenic conditions, including post-menopausal osteoporosis. The purpose of this study was to determine the ability of PTH to stimulate bone formation in the mandibles of aged ovariectomized (Ovx) rats, and the results are compared with a site in the appendicular skeleton (humerus). The Ovx rat is a useful model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 21 publications
6
44
0
Order By: Relevance
“…Intermittent parathyroid hormone administration was also shown to induce an increase in alveolar bone formation in rats. 25 In the present study, alveolar bone width of the ZA group was found to be greater than that of the control group. This finding might be the result of the inductive effect of BRONJ lesion on periosteal new bone formation.…”
Section: Discussionsupporting
confidence: 41%
“…Intermittent parathyroid hormone administration was also shown to induce an increase in alveolar bone formation in rats. 25 In the present study, alveolar bone width of the ZA group was found to be greater than that of the control group. This finding might be the result of the inductive effect of BRONJ lesion on periosteal new bone formation.…”
Section: Discussionsupporting
confidence: 41%
“…In animal studies the anabolic action of PTH has frequently been confirmed [13][14][15][16][17][18][19][20] and improvement in the physical properties of the bone reported [21]. Such an anabolic action appears to depend on the intact Nterminal portion of PTH, since the effect almost disappeared on removal of one N-terminal amino acid [22][23].…”
Section: Discussionmentioning
confidence: 90%
“…Because one of the basic characteristics of periodontitis is the resorption of alveolar bone, it was hypothesized that PTH could inhibit bone resorption and promote alveolar bone regeneration, thereby representing a promising potential technique for improving the outcome of periodontal therapy. Miller et al (1997) administered intermittent PTH to the mandibles of aged ovariectomized rats and found that PTH stimulated bone formation in the mandible [237]. Similarly, using a ligature-induced periodontitis model in rodents, another group found that PTH protects against periodontitis-associated bone loss [238].…”
Section: Parathyroid Hormonementioning
confidence: 99%